(untitled) (Research, Society and Development, 2024)
Entamoeba histolytica is the cause of amoebiasis, a neglected tropical disease and a leading cause of mortality worldwide. The objective of this review is to show the potential of probiotics as a treatment strategy for amoebiasis. A systematic search was conducted using PubMed and Google Scholar with keywords "Entamoeba histolytica", "amoebiasis", and "probiotics." The studies on probiotics for amoebiasis treatment are limited, but some shown promising results. Lactobacillus acidophilus reduced E. histolytica cyst excretion by 79.67% in mice, with a 68.31% efficacy comparable to metronidazole. Bifidobacterium sp. showed 75.63% efficacy in reducing infection severity, higher than metronidazole (67.56%). Lactobacillus salivarius inhibited E. histolytica growth in vitro and provided protection in vivo. Lactobacillus fermentum and L. delbrueckii inhibited E. histolytica proliferation with efficacy ranging from 46.42% to 97.68%, depending on the concentration. Saccharomyces boulardii reduced amoebic dysentery duration by 25% and eliminated parasitic cysts in human stool samples. Lactobacillus casei showed a 100% recovery rate in rats infected with E. histolytica. These findings suggest probiotics have potential as therapeutic agents for amoebiasis, but further research is needed to confirm their effectiveness in animal models and humans.